2017
DOI: 10.3198/jpr2016.09.0042crmp
|View full text |Cite
|
Sign up to set email alerts
|

Registration of Wyandot × PI 567301B Soybean Recombinant Inbred Line Population

Abstract: A soybean [Glycine max (L.) Merr] mapping population, Wyandot × PI 567301B (Reg. No. MP‐5, NSL 519221 MAP), consisting of 357 F7–derived recombinant inbred lines (RILs) was jointly developed by the USDA‐ARS and the Ohio Agricultural Research and Development Center in Wooster, OH. The population was developed by single seed descent from a cross between ‘Wyandot’ and PI 567301B. Wyandot is a food‐grade cultivar released by The Ohio State University, and PI 567301B is a plant introduction from China that differs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…In 2015, the 621 accessions (Table S1) were planted in three mid-western and one southern locations of the USA [Wooster (OHW15) and Columbus, OH (OHC15), Urbana, IL (IL15) and Plymouth, NC (NC15)] with two replications at each environment in an augmented randomized complete block design (ARCBD). Each replicate within the ARCBD was divided into 4 blocks, which included no more than 196 accessions and four checks: ‘Summit’ (McHale et al 2013 ), ‘Wyandot’ (Lee et al 2017 ; https://mchalelab.cfaes.ohio-state.edu/sites/mchale/files/imce/Wyandot_release_document.pdf ), HR09-397 (a high protein breeding line from USDA-ARS, Wooster, OH) and ‘Prohio’ (Mian et al 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…In 2015, the 621 accessions (Table S1) were planted in three mid-western and one southern locations of the USA [Wooster (OHW15) and Columbus, OH (OHC15), Urbana, IL (IL15) and Plymouth, NC (NC15)] with two replications at each environment in an augmented randomized complete block design (ARCBD). Each replicate within the ARCBD was divided into 4 blocks, which included no more than 196 accessions and four checks: ‘Summit’ (McHale et al 2013 ), ‘Wyandot’ (Lee et al 2017 ; https://mchalelab.cfaes.ohio-state.edu/sites/mchale/files/imce/Wyandot_release_document.pdf ), HR09-397 (a high protein breeding line from USDA-ARS, Wooster, OH) and ‘Prohio’ (Mian et al 2008 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because South Korean accessions with potential novel Rps genes are also genetically distant from U.S. genotypes (Burnham et al, 2002), the use of these accessions in breeding programs has the potential to expand the diversity of U.S. soybean cultivars. However, expanding the diversity of soybean can often result in the introgression of other yieldlimiting traits; therefore, molecular markers that are associated with the Rps genes are needed (Carter et al, 2004;Lee et al, 2017). This study sought to identify and map new Rps loci in the PIs 407974B and 424487B because they all contained more than one Rps gene.…”
Section: Core Ideasmentioning
confidence: 99%
“…Cross validation analysis showed that high predictive abilities for protein, oil could be achieved with these markers, while a larger training set size in combination with increased genetic relatedness between training and validation set could further improve predictive ability of seed yield. In addition, the 6K assay has been used to map agronomy traits in nested association mapping populations (Beche et al ., 2020), to estimate population structure, pedigree and LD (Contreras‐Soto et al ., 2017), and characterize the mapping population for registration (Lee et al ., 2017). The assay has been proven useful and efficient by the soybean breeders and geneticists working in the private and public sectors, and the assay was commercialized by Illumina (http://www.illumina.com/areas-of-interest/agrigenomics/consortia.html).…”
Section: Discussionmentioning
confidence: 99%